The Impact of Digital Technology on the Role of Librarians in Higher Education (A Challenge, Opportunity, and Transformation) - Subchan, Nur (Brawijaya University Library, 2023)
This research aims to understand the impact of the shift to digital technology on the work of university librarians, identify strategies to stay relevant in the digital age, and improve library services. This study uses a qualitative approach with a case study method, collects data through interviews with university librarians who experience changes due to digital technology, and analyzes related documents and literature to identify their patterns, challenges, and strategies in dealing with these changes. This research showed that the shift to digital technology has had a significant impact on the role of university librarians. Librarians must now manage electronic resources and develop new skills, such as information technology, metadata management, and digital preservation. They also need to be able to navigate the complex digital information landscape, promote electronic resources, and collaborate with users in the development of digital resources. In addition to technical ability, librarians must be creative and innovative, willing to experiment with new approaches and technologies, and look at problem-solving options. Innovation is key to staying relevant in the digital age. Previous studies have also highlighted the importance of collaboration with users and a focus on community needs as important elements in developing effective library services. This research reveals that the shift to digital technology has significantly changed the role of university librarians. They must develop in technology skills, collaborate with users, and be innovative in facing digital challenges. The ability to manage, promote electronic resources, and understand community needs is important in maintaining the relevance of librarians in the digital age.